Effects of light sources and drying methods on plant growth and steviol glycosides content of stevia (Stevia rebaudiana Bertoni) - Rashid, Mohd Aziz (2017)
Stevia (Stevia rebaudiana Bertoni) has received great attention with the rise in demand for low-sugar food and beverage additives, and natural alternative to sugarcane sugar and artificial sweeteners. The leaves produce intensively sweet steviol glycosides (mainly stevioside and rebaudioside A). Stevia is an obligate short-day plant with a critical daylength of 13 h. Daylength in Malaysia which is less than 13 h causes stevia to flower early, resulting in a low leaf yield and a low percentage of sweetener content. In the first experiment, the effects of night interruption technique using incandescent, fluorescent cool day light (C.D.L.), fluorescent warm white (W.W.), light-emitting diode (LED) C.D.L. and LED W.W. for 60 min daily to lengthen vegetative phase, on plant biomass and steviol glycoside content of stevia were investigated. The study was carried out using a nested design with a 6 x 4 factorial arrangements of six light sources and four growing weeks after night interruption initiated (week 2, 4, 6 and 8) with four replications. Results showed that night interruption technique extended vegetative phase from 20 days (control) to 120 days; thus allowing accumulation of plant biomass and steviol glycosides content. Leaf biomass and steviol glycosides of all light sources treated plants increased significantly as compared to control plants especially in week 6 and 8. Fluorescent W.W. can be considered as the best light source for night interruption technique of stevia as total steviol glycosides content per plant increased by 190-270% as compared to other light sources. The second experiment was conducted to determine the effects of several drying methods on steviol glycosides content of stevia leaves. Six drying method treatments were arranged in a completely randomized design (CRD) with four replications. Stevioside content was not significantly affected by the drying of sun, air, oven and freeze at different temperature to obtain pre-determined moisture content (MC). However, rebaudioside A content was significantly reduced by 3.38% under oven drying at 70 °C to obtain 10% MC. The reduction indicated that thermal degradation of rebaudioside A occured at higher temperature. In conclusion, sun drying is the easiest and cheapest technique to dry stevia leaves without causing significant reduction of stevioside and rebaudioside A.